Comprehensive Review on Hemorrhoids: From Epidemiology to Preclinical Assessment of Anti-Hemorrhoidal Agents (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The review discusses the etiology, epidemiology, classification, risk factors, assessment, the role of biomarkers in the development of hemorrhoids, operative and non-operative treatment options, post-operative complications of hemorrhoids, preclinical evaluation methods of anti-hemorrhoidal drugs, and different medicinal plants that exhibit anti-hemorrhoidal activity. The dilation and dislocation of normal anal cushions characterizes hemorrhoids. One of the most significant discoveries regarding hemorrhoids is the atypical enlargement and distortion of blood vessels, along with damage and modifications to the anal cavity’s supporting connective tissue. Hemorrhoids are categorized into different classifications based on various factors, Golingher’s classification commonly used, which divides the hemorrhoidal condition into four grades according to prolapse and the development of hemorrhoids. Hemorrhoids are recognized as one of the leading causes of morbidity, affecting millions of populations worldwide and also increasing the economic burden on the healthcare system. Current treatment options for hemorrhoids often involve conservative approaches, including fiber supplements, anti-inflammatory medications, lifestyle changes, and venotonic medicines. Additionally, operative treatments like rubber band ligation, hemorrhoidectomy, and injection sclerotherapy are utilized. Various biomarkers are responsible for the occurrence of hemorrhoids, such as matrix metalloproteinase (MMP), vascular endothelial growth factor (VEGF), inducible nitric oxide synthase (iNOS), and C-reactive protein (CRP). These biomarkers hold potential as targets for developing new anti-hemorrhoidal agents.